PENGARUH PENGETAHUAN TENTANG SANITASI LINGKUNGAN TERHADAP KUALITAS KESEHATAN LINGKUNGAN RUMAH DI KEBAYORAN LAMA UTARA - Yuvita Cornelya Said; Nur hayati; Deni Kurniawan (FT-USNI, 2020)
The increasing rate of urban population growth equates to the increasing pressure placed on theenvironment due to the need for natural resources and land availability. Limited residential land has ledto the construction of slum densely populated settlements and a lack of knowledge about environmentalsanitation which affects the physical condition and environmental health quality of the house. The purposeof this study was to determine the effect of knowledge about environmental sanitation on the health qualityof the home environment in Kebayoran Lama Utara Village. The research method used in this research isa survey method with a quantitative approach. The results showed that there was an effect of knowledgeabout environmental sanitation on the health quality of the home environment, with the results of thecorrelation analysis 0.997 with a determination coefficient of 99.4%, the regression line equation Ŷ = -0.248 + 1.958 X, the significance test of tcount> ttable = 98.493> 1.67 and significance testing of the valueof Fcount> Ftable = 9700.595> 4.00.